The Effect of Green Bean Porridge and Boiled Eggs on Malnourished Toddlers 2-5 Years to Gain Weight - Amanda, Nova; Adriyani, Fauziah Hanum Nur; Hikmanti, Arlyana (An Idea Health Journal, 2025)
Toddles are a period of physical, congnitve. The age of toddlers ranges from 1 to 5 years, this age is exceptionally critical for a child's development and improvement so it is called the golden age. The most frequent nutritional problem s malnutrtion. Young children who experience malnutrition from of 2-5 years old for a long period of time wiil exxperience a thin body and experience problems whit the growth and brain tissue, which can affect the level ofbrain intelligence. The general aim of preparing this report is to conduct a case study regarding giving green bean porridge andboiled eggs to malnourished toddlers aged 2-5 years to gain weight. The method used was to 5 undernourished In Rakit 1 health center i, infants aged 2-5 years are observed for 10 days. providing green bean porridge and boiled eggs. This case study was carried out through interviews and providing eating observation A document designed to measure the weight of children who are undernourished.The outcomes of the program. green bean porridge and boiled eggs, there were 4 small children who experienced improvement body wight , 1 did not experince an increase in body wight. These result can beseen from the average increase in toddler weight 0,59 Kg